Recurrent innovation of protein-protein interactions in the drosophila piRNA pathway - Riedelbauch, Sebastian; Masser, Sarah; Fasching, Sandra; Lin, Sung-Ya; Salgania, Harpreet Kaur; Aarup, Mie; Ebert, Anja; Jeske, Mandy; Levine, Mia T; Stelzl, Ulrich; Andersen, Peter (The EMBO journal, 2025)
Despite being essential for fertility, genome-defense-pathway genes often evolve rapidly. However, little is known about the molecular basis of this adaptation. Here, we characterized the evolution of a protein interaction network within the PIWI-interacting small RNA (piRNA) genome-defense pathway in Drosophila at unprecedented scale and evolutionary resolution. We uncovered the pervasive rapid evolution of a protein interaction network anchored at the heterochromatin protein 1 (HP1) paralog Rhino. Through cross-species high-throughput yeast-two-hybrid screening, we identified three distinct evolutionary protein interaction trajectories across ~40 million years of Drosophila evolution. While several protein interactions are fully conserved, indicating functional conservation despite rapid amino acid-sequence change, other interactions are preserved through coevolution and were detected only between proteins within or from closely related species. We also identified species-restricted protein interactions, revealing insight into the mechanistic diversity and ongoing molecular innovation in Drosophila piRNA production. In sum, our analyses reveal principles of interaction evolution in an adaptively evolving protein-protein interaction network, and support intermolecular interaction innovation as a central molecular mechanism of evolutionary adaptation in protein-coding genes.
Gesehen am 26.11.2025